LEARNING INNOVATIONS OF THE COVID-19 PANDEMIC TIME ISLAMIC EDUCATION (PAI) IN SEKOLAH DASAR NEGRI 9 KAMPUNG BARU KECAMATAN SIMPANG EMPAT KABUPATEN TANAH BUMBU KALIMANTAN SELATAN - Ranah (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
The main factor in this study aims to find out what learning innovations were carried out during the Covid-19 pandemic, then what is the impact of implementing learning innovations, and want to see them supporting and inhibiting factors for implementing learning innovations carried out by the 9 Kampung Baru Elementary School, Simpang District. Four districts of Tanah Bumbu, South Kalimantan. This research uses a qualitative approach. The results showed that the learning innovations that were carried out were emphasized on: First, the delivery of Islamic Religious Education materials that applied four learning innovations, namely the Contextual Teaching and Learning (CTL) strategy, PowerPoint media, mobile communication media, and social media as well as a religious practice competition. Second, the impact of implementing learning innovations during the Covid-19 pandemic can be seen in the following two things: a) students become trained to relate lessons learned with what is happening in the environment at that time, b). Changes in student attitudes are getting better. Third, Supporting Factors and Inhibiting Factors for the implementation of Learning Innovation in Islamic Religious Education Subjects: 1) the supporting factors for PAI learning innovation are as follows: a. Teacher ability. b). Students' abilities. c). Facilities and infrastructure. 2). Inhibiting factors in the implementation of learning innovation, among others, are as follows: a) Teacher limitations. b) Inadequate facilities and infrastructure. c). Students' diverse psychological abilities and souls.